Analysis of recrystallization behavior of hot-deformed austenite reconstructed from electron backscattering diffraction orientation maps of lath martensite. (February 2016) - Kubota, Manabu; Ushioda, Kohsaku; Miyamoto, Goro; Furuhara, Tadashi
Abstract: The recrystallization behavior of hot-deformed austenite of a 0.55% C steel at 800 °C was investigated by a method of reconstructing the parent austenite orientation map from an electron backscattering diffraction orientation map of lath martensite. Recrystallized austenite grains were clearly distinguished from un-recrystallized austenite grains. Very good correlation was confirmed between the static recrystallization behavior investigated mechanically by double-hit compression tests and the change in austenite microstructure evaluated by the reconstruction method. The recrystallization behavior of hot-deformed 0.55% C steel at 800 °C is directly revealed and it was observed that by addition of 0.1% V the recrystallization was significantly retarded. Graphical abstract: